Seasonal development and ovipositing behavior of Marchalina hellenica (Hemiptera: Margarodidae) - Gounari, Sofia (ENTOMOLOGIA HELLENICA, 2004)
Marchalina hellenica, Gennadius (Hemiptera: Margarodidae) is the main honeydew producing insect of pine trees ίη Greece. Its behavior during oviposition, the reproductive capacity, oviposition period, pre-hatching period, and life span of the οviposited female and other aspects of its reproductive behavior in the field and in the laboratory, have been recorded in a three-year research. Μ. hellenica completes one generation per year. It is mainly parthenogenetic. The adult female appears on the trees, looking for an oviposition site from late March to late April. Its oviposition period in the field lasts about 20 days, while the hatching period lasts about 30 days. Live females can be found on the trees until the end of May, so there is a coexistence of three stages of Μ. hellenica, adult, eggs and 151 stage nymphs, in the field for about one month. Μ. hellenica is able to oviposit in the laboratory in room conditions. Its ovipositing period is as long as 16 days, while the total number of eggs laid is on average 262. Body weight was significantly correlated with the total number of eggs laid.